PENGARUH PERMAINAN MEMANCING IKAN MAS KOKI UNTUK KEMAMPUAN MENGENAL HURUF ANAK DI TAMAN KANAK-KANAK AISYIYAH 14 PADANG - Fitriyanti, Anggi; Rakimahwati; Yulsyofriend; Anggraini, Vivi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the goldfish fishing game on children's letter recognition ability at TK Aisyiyah 14 Padang. This research employed a quantitative approach with a quasi-experimental design, specifically a pretest-posttest control group design. The subjects were group A kindergarten children divided into experimental and control classes. Data were collected through observation and letter recognition tests, including identifying letter shapes, naming letters, and associating letters with sounds.The results showed a significant improvement in children's letter recognition ability after the implementation of the goldfish fishing game. This finding is supported by previous studies indicating that activity-based games such as alphabet fishing significantly improve children's letter recognition skills . Therefore, the goldfish fishing game can be used as an effective and enjoyable learning medium to enhance early literacy skills in early childhood education.